The Green Economy and Sustainability in Islam - Harianto, Harianto; Ladaina, M. Satria; Panorama, Maya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Environmental problems have serious implications for sustainable development and community welfare, as well as affecting Maqasid Syariah. The environment is closely related to institutions and economic growth. This research examines the concept of a green economy from a sharia perspective as a recommendation for sustainable development in Indonesia. The research uses qualitative methods with literature research in the form of journals and related documents. The research results show that the green economy is part of Maqasid Syariah because it prioritizes benefit, poverty alleviation, ecosystem protection and job creation. Islamic environmental ethics is reflected in the green economy, which aims to manage natural resources sustainably. The success of a green economy depends on the consistency of government policies